2016
DOI: 10.1159/000448922
|View full text |Cite
|
Sign up to set email alerts
|

Study of <b><i>hTERT</i></b> and Histone 3 Mutations in Medulloblastoma

Abstract: Hotspot activating mutations of the telomerase reverse transcriptase (hTERT) promoter region were recently described in several tumor types. These mutations lead to enhanced expression of telomerase, being responsible for telomere maintenance and allowing continuous cell division. Additionally, there are alternative telomere maintenance mechanisms, associated with histone H3 mutations, responsible for disrupting the histone code and affecting the regulation of transcription. Here, we investigated the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Hotspot h TERT somatic mutations have been reported in medulloblastomas with frequencies ranging 4–27% . In the present study, h TERT mutations were observed in 29% of the cases, and these mutations were more frequent in MB SHH as previously described Moreover, h TERT mutations were associated with older‐aged patients in accordance with previous studies .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hotspot h TERT somatic mutations have been reported in medulloblastomas with frequencies ranging 4–27% . In the present study, h TERT mutations were observed in 29% of the cases, and these mutations were more frequent in MB SHH as previously described Moreover, h TERT mutations were associated with older‐aged patients in accordance with previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…Hotspot h TERT somatic mutations have been reported in medulloblastomas with frequencies ranging 4–27% . In the present study, h TERT mutations were observed in 29% of the cases, and these mutations were more frequent in MB SHH as previously described Moreover, h TERT mutations were associated with older‐aged patients in accordance with previous studies . Since h TERT ‐activating promoter mutations are reported to enhance telomerase expression, we included the h TERT gene in the CodeSet of the 22‐gene panel for medulloblastoma molecular subgrouping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations